(untitled) (International Journal of Architecture and Urbanism, 2022)
Lake Toba is the largest caldera lake in the world, so its development is included in the 5 super priority areas for the development of the tourism sector. This study aims to identify and analyze the morphology that appears in the travel routes in Lake Toba. This study uses qualitative methods with a descriptive approach to explain and interpret travel routes in Lake Toba. The substance boundaries discussed in this study are components and morphological forms. The morphological component is land use, road network patterns/travel routes, and buildings (density and patterns).